1961
DOI: 10.1042/bj0780435
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on the paraffins and primary alcohols of plant waxes

Abstract: BIOSYNTHESIS OF POLYNUCLEOTIDES 435 5. In a period of 15 min., adenosine 5'-di-and-tri-phosphate, but not adenosine 5'-monophosphate, suppress the incorporation of [32p] orthophosphate into only the adenosine 5'-monophosphate residues of ribonucleic acid. The authors are indebted to the British Empire Cancer Campaign for financial support and one of them (M.J.) thanks the Department of Scientific and Industrial Research for a maintenance grant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1963
1963
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Thus for the first time the complex nature of the alkane fraction was revealed [3]and the presence of large quantities of iso-alkanes demonstrated besides the more usual normal alkanes. These findings have been confirmed [4] and elegantly extended recently [5]. The alcohol fraction has been shown to contain stigmasterol, Pand ')I-sitosterol [6], solanesol, and n-docosanol [7].…”
mentioning
confidence: 68%
“…Thus for the first time the complex nature of the alkane fraction was revealed [3]and the presence of large quantities of iso-alkanes demonstrated besides the more usual normal alkanes. These findings have been confirmed [4] and elegantly extended recently [5]. The alcohol fraction has been shown to contain stigmasterol, Pand ')I-sitosterol [6], solanesol, and n-docosanol [7].…”
mentioning
confidence: 68%
“…As expected, the major alkanes of the leaf waxes were C29 and C31. The hydrocarbon compositions of leaf wax from rutabaga (Waldron et al, 1961), red beet (Strfinsk) et al, 1967) and carrot (Nishimoto, 1973) have been previously reported. The results of the first two studies agree with our findings, whereas in the case of carrot leaves our results showed that n-C29 is the major alkane but n-C2v was previously reported to be the major alkane.…”
Section: Hydrocarbonsmentioning
confidence: 90%
“…Chibnall and colleagues later verified this early finding by mass spectroscopy. 2 Our initial studies in 1975 showed that coarsely chopped alfalfa increased the growth of plants when applied as a sidedressing in a band below and to the side of the crop seeds or seedlings. 3 An application of 117 kg of dry alfalfa per hectare increased early tomato (Lycopersicon esculentum) yields by 10 metric tons per hectare.…”
Section: Introductionmentioning
confidence: 99%